Master tracks in different resolutions of HEINCKE cruise HE665, Bremerhaven - Bremerhaven, 2025-07-26 - 2025-07-28 - Koch, Boris P (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2025)
Raw data acquired by position sensors on board RV Heincke during expedition HE665 were processed to receive a validated master track which can be used as reference of further expedition data. During HE665 the inertial navigation system IXSEA PHINS III and the GPS receivers Trimble Marine SPS461 and SAAB R5 SUPREME NAV were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.awi.de) with a resolution of 1 sec. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.